The prevalence of Helicobacter pylori primary resistance towards antibiotics using an Epsilometer-test method - Mohamad Zin, Noraziah; Hanafiah, Alfizah; Abdul Rahim, Mohd Badrin Hanizam; Kamaruddin, Muhamad Mazlan; Abu Bakar, Nur Faizah (Universiti Sains Malaysia, 2018)
An epsilometer-test method was used to determine MIC values of several antibiotics against 29 Helicobacter pylori isolated from gastric antrum of dyspepsia patients. Isolates with resistance towards antibiotics were 6.9% -65.5% but these were tetracycline-sensitive. Eight isolates showed multi-resistance towards two antimicrobial agents. The high resistance strains towards metronidazole is alarming.